Painful reminders: Involvement of the autobiographical memory system in pediatric postsurgical pain and the transition to chronicity - Anna Waisman; Maria Pavlova; Melanie Noel; Joel Katz (Taylor & Francis Group, 2022)
Memory biases for previous pain experiences are known to be strong predictors of postsurgical pain outcomes in children. Until recently, much research on the subject in youth has assessed the sensory and affective components of recall using single-item self-report pain ratings. However, a newly emerging focus in the field has been on the episodic specificity of autobiographical pain memories. Still in its infancy, cross-sectional work has identified the presence of various memory biases in adults living with chronic pain, one of which concerns the lack of spatiotemporal specificity. Moreover, a recent prospective longitudinal study found that adults scheduled for major surgery who produced fewer specific pain memories before surgery were at greater risk of developing chronic postsurgical pain up to 12 months later. The present review draws on this research to highlight the timely need for a similar line of investigation into autobiographical pain memories in pediatric surgical populations. We (1) provide an overview of the literature on children's pain memories and underscore the need for further research pertaining to memory specificity and related neurobiological factors in chronic pain and an overview of the (2) important role of parent (and sibling) psychosocial characteristics in influencing children's pain development, (3) cognitive mechanisms underlying overgeneral memory, and (4) interplay between memory and other psychological factors in its contributions to chronic pain and (5) conclude with a discussion of the implications this research has for novel interventions that target memory biases to attenuate, and possibly eliminate, the risk that acute pain after pediatric surgery becomes chronic.